The object of literature - Macherey, Pierre 1938- (Literature, culture, theory, 1995)
Continuing the project of Althusserian theory, Macherey engages in a series of close exegeses of classical texts in French literature and philosophy, from the late eighteenth century down to the 1970s, that explore the historically variable but thematically similar ways in which literary texts represent philosophical topoi in an unmediated manner, Macherey shows the conceptual sophistication - and broad intellectual influence - that literary art has displayed in the modern period